JARINGAN SOSIAL PETANI KOPI DI LMDH KARAMAT JAYA KECAMATAN CISURUPAN KABUPATEN GARUT - Nanda Putri Aulia; Ahmad Choibar Tridakusumah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
LMDH Karamat Jaya is a community institution in Kramatwangi Village, Cisurupan District, Garut Regency which was initiated by the PHBM (Community Forest Management) program. In coffee farming, farmers at LMDH Karamat Jaya experience limitations in obtaining productive resources, so that the potential and production yields are less than optimal due to the lack of relationships and relationships between farmers and other coffee actors. This study aims to: 1) identify the characteristics of coffee farmers in LMDH Karamat Jaya, and 2) analyze the social network structure of coffee farmers in LMDH Karamat Jaya. Informants were selected by the Snowball sampling technique. The research method used is qualitative with a case study approach. Data analysis used descriptive and Social Network Analysis (SNA). The results show that the social network structure of coffee farmers in LMDH Karamat Jaya forms an interlocking personal network and the actors who play an important role in the network are the LMDH Supervisory Board as well as the Village Head and members of LMDH Karamat Jaya who are a dealer/coffee collector.